Perilaku Konsumsi Garam Dan Gula Pada Mahasiswa Fakultas Kedokteran Universitas Tadulako Angkatan 2020 - Georgiana Patricia Tangkilisan; Fitriah Handayani; Ketut Suarayasa; Yuli Fitriana (Yayasan Literasi Sains Indonesia, 2022)
The objective of this research is to find out the knowledge, attitudes, and behavior of sugar and salt consumption among students at the medical faculty of Tadulako University in the 2020 batch. Methods: This research method is descriptive quantitative. The sample totaled 157 respondents selected through the total sampling technique. Results: A total of 156 respondents filled out the questionnaire. The results of the research are as follow: Students who have good knowledge about sugar and salt consumption on age 17 to 19 years of 66.4%, age 20 to 22 years of 68.2%. The characteristic of gender which has good knowledge about sugar and salt consumption is female of 71.3%, male of 50%. The characteristic of age which has a positive attitude about consuming sugar and salt is 17-19 years of 100%, 20-22 years of 95.5%. The female gender has a positive attitude about sugar and salt consumption of 99%, the male is 100%. Aged 17-19 years have positive behavior about consuming sugar and salt of 98.5%; age 20-22 years of 95%. The female gender has positive behavior regarding sugar and salt consumption of 97.5%; male of 100%. The top three foods frequently consumed by respondents were Siomay (16.4%), Indomie fried noodle (15.7%), and fried rice (10%). The top three drinks frequently consumed by the respondents are Pop-Ice (18.4%), Nutrisari Orange (16.9%), and Orange Juice (15.4%). Conclusion: There is good knowledge, positive attitudes and positive behavior about salt and sugar consumption in medical students at the medical faculty of Tadulako University in the 2020 batch.